Security and Dependability for Ambient Intelligence - Spanoudakis, George; Kokolakis, Spyros (Advances in Information Security, 2009)
Security and Dependability for Ambient Intelligence is the primary publication of the SERENITY approach, which provides security and dependability (S&D) solutions for dynamic, highly distributed, heterogeneous systems. The objective of SERENITY is to enhance the security and dependability of ambient intelligence systems by providing a framework supporting the automated integration, configuration, monitoring and adaptation of security and dependability mechanisms. An edited volume contributed by world leaders in the field, this book covers the problems that the highly dynamic and heterogeneous nature of ambient intelligence systems poses to security and dependability and presents solutions to these problems. Security and Dependability for Ambient Intelligence is designed for researchers and practitioners focusing on the dynamic integration, deployment and verification of security and dependability solutions in highly distributed systems incorporating ambient intelligence features. It is also suitable as a reference or secondary text for advanced-level students in computer science and computer or electrical engineering. .